Ultra-inert lanthanide chelates as mass tags for multiplexed bioanalysis - David, Tomáš; Šedinová, Miroslava; Myšková, Aneta; Kuneš, Jaroslav; Maletínská, Lenka; Pohl, Radek; Dračínský, Martin; Mertlíková-Kaiserová, Helena; Čížek, Karel; Klepetářová, Blanka; Litecká, Miroslava; Kaňa, Antonín; et al. (Nature communications, 2024)
Coordination compounds of lanthanides are indispensable in biomedical applications as MRI contrast agents and radiotherapeutics. However, since the introduction of the chelator DOTA four decades ago, there has been only limited progress on improving their thermodynamic stability and kinetic inertness, which are essential for safe in vivo use. Here, we present ClickZip, an innovative synthetic strategy employing a coordination-templated formation of a 1,5-triazole bridge that improves kinetic inertness up to a million-fold relative to DOTA, expanding utility of lanthanide chelates beyond traditional uses. Acting as unique mass tags, the ClickZip chelates can be released from (biological) samples by acidic hydrolysis, chromatographically distinguished from interfering lanthanide species, and sensitively detected by mass spectrometry. Lanthanides enclosed in ClickZip chelates are chemically almost indistinguishable, providing a more versatile alternative to chemically identical isotopic labels for multiplexed analysis. The bioanalytical potential is demonstrated on tagged cell-penetrating peptides in vitro, and anti-obesity prolactin-releasing peptides in vivo.
Keywords: Triazoles; kinetika; Contrast Media; kontrastní látky; chelátory; Mass Spectrometry; Mice; Lanthanoid Series Elements; lanthanoidy; magnetická rezonanční tomografie; Magnetic Resonance Imaging; zvířata; triazoly; Humans; Kinetics; myši; Chelating Agents; hmotnostní spektrometrie; lidé; Animals